Community Perception of Covid-19 Booster Dose Vaccines in Klampis Sub-District Bangkalan District - Nadiya Istighfaara; Ira Nurmala; Mohammad Zainal Fatah (Budapest International Research and Critics University, 2022)
This study aims to determine the perception of vaccine recipients in the klampis sub-district, Bangkalan district. This qualitative research uses a case study design. Respondents in this study used 7 respondents. The results of the study concerning community perception of the COVID-19 booster dose vaccination in Klampis, Bangkalan District showed both positive and negative perceptions. But, overall this study is that the public acceptance of the booster dose vaccine is quite good.